Idiopathic Intracranial Hypertension (Pseudotumor Cerebri). Issue 6 (December 2016) - Bell, Susan
Abstract : ABSTRACT: Idiopathic intracranial hypertension has been recognized in the literature for over 100 years. It is a disease of elevated intracranial pressure without evidence of a space-occupying lesion found most often in obese women of childbearing age. The signs and symptoms have been well described; however, the etiology is yet unknown. Medical and surgical treatment is aimed at the preservation of vision and improvement in symptoms. The medical literature is replete with articles addressing the epidemiology, pathophysiology, clinical and imaging features, and treatment. There are limited nursing reports (Lehman, 2003 ;McDonald, 1984 ;Revta, 1977 ). The objective of this manuscript is to provide an overview for the neuroscience nurse of the clinical features, diagnostic work-up, and therapeutic options available for patients with idiopathic intracranial hypertension.